Effects of high-intensity interval and moderate-intensity continuous aerobic exercise on diabetic obese patients with nonalcoholic fatty liver disease: A comparative randomized controlled trial - Abdelbasset, Walid Kamal (Medicine (Baltimore), 2020)
BACKGROUND: Some studies assessed the effect of aerobic exercise on diabetic obese patients with hepatic disease, while very limited studies compared high-intensity interval (HII) versus moderate-intensity continuous (MIC) on diabetic obese patients with non-alcoholic fatty liver disease (NAFLD). OBJECTIVES: This study was designed to assess the effects of HII versus MIC on intrahepatic triglycerides (IHTG) and visceral lipids in diabetic obese patients with NAFLD. DESIGN: Randomized controlled trial. METHODS: Forty-seven diabetic obese individuals with NAFLD were enrolled in this study. The individuals were randomly divided into 16 in HII group, 15 in MIC group, and 16 in the controls. HII group received HII exercise, MIC group received 8-week MIC exercise while the control group did not receive any exercise intervention. IHTG and visceral lipids were assessed pre- and post-intervention. RESULTS: Baseline and clinical characteristics showed nonsignificant difference among the 3 groups (P > .05). Both HII and MIC groups showed a significant reduction in hepatic fat and visceral lipids (P < .05), while the controls showed nonsignificant difference (P > .05) after completing the study intervention. Postintervention analysis showed nonsignificant changes between the HII and MIC groups (P > .05). CONCLUSIONS: Exercise training wither HII or MIC aerobic exercise reduces IHGT and visceral lipids in diabetic obese patients with NAFLD. No differences were observed between the effects of both exercise programs on diabetic obese patients with NAFLD.